2018
DOI: 10.1097/md.0000000000011895
|View full text |Cite
|
Sign up to set email alerts
|

Exploring prognostic genes in ovarian cancer stage-related coexpression network modules

Abstract: Identification of meaningful cluster modules of differential genes or representative biomarkers related to the stages of ovarian cancer (OC) is pivotal, which may help to detect mechanisms of OC progression and evaluate OC patients’ prognosis.We downloaded gene expression data and the corresponding clinical information of OC patients from The Cancer Genome Atlas (TCGA) database, which included 379 ovarian cancer patients. Differentially expressed genes (DEGs) of OC patients between stages were picked out using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Studies indicated that COL3A1 is highly correlated with tumor progression and metastasis [ 20 , 21 ]. COL3A1 has been identified as a representative biomarker that is overregulated in the focal adhesion pathway, and plays an unfavorable role in the development and metastasis of ovarian and bladder cancer [ 22 , 23 ]. A previous study demonstrated that the mRNA and protein levels of COL3A1 are not only present in colorectal cancer (CRC) cells, but also increased in the plasma of CRC patients, which is associated with clinicopathologic factors and poor survival [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that COL3A1 is highly correlated with tumor progression and metastasis [ 20 , 21 ]. COL3A1 has been identified as a representative biomarker that is overregulated in the focal adhesion pathway, and plays an unfavorable role in the development and metastasis of ovarian and bladder cancer [ 22 , 23 ]. A previous study demonstrated that the mRNA and protein levels of COL3A1 are not only present in colorectal cancer (CRC) cells, but also increased in the plasma of CRC patients, which is associated with clinicopathologic factors and poor survival [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the data set of OV, 67 genes were identified by univariate Cox regression to be significantly associated with the cancer (Table 3) and seven of them, namely COL1A1, COL3A1, RPL10, ARHGAP5, LATS1, TSHR and SLC34A2, were found in the CGC data set. Genes COL1A1 and COL3A1 are demonstrated that played an unfavorable role in the development of ovarian cancer, and could be considered as the prognostic genes of OV [45]. Moreover, COL1A1 has also been found to be positively related with the degree of invasion, metastasis, and advanced stages of gastric cancer [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Genes COL1A1 and COL3A1 are demonstrated that played an unfavorable role in the development of ovarian cancer, and could be considered as the prognostic genes of OV [45]. Moreover, COL1A1 has also been found to be positively related with the degree of invasion, metastasis, and advanced stages of gastric cancer [45,46]. COL3A1 can also be considered to be a potential biomarker for colon cancer [47], breast cancer [48] and brain tumor [49].…”
Section: Discussionmentioning
confidence: 99%
“…[17] Cytohubba is a tool that provides 11 topological analysis and 6 centralities based on shortest paths to detect the hub genes (key genes). [18]…”
Section: Methodsmentioning
confidence: 99%